SMEs’ Trade Zakat Payment for Poverty Alleviation: Study Case in Malang City, Indonesia - Marlina Ekawaty; Muhammad Hakimi Mohd Shafiai; Ajeng Kartika Galuh; Rachmad Kresna Sakti; Helmy Aulia Rachman; Ghifary Duyufur Rohman; Amalia Rahmawati (International Journal Of Community Service, 2025)
This community service program aims to enhance SMEs' understanding of trade zakat and improve their compliance with zakat obligations in Malang City. Using a quantitative approach and Structural Equation Modeling (SEM), the study analyzes data collected from SME owners in Malang. The program addresses key factors influencing willingness to pay zakat, including entrepreneurs’ attitudes, zakat literacy, and the role of zakat administrators. The program consists of training sessions that cover the importance and potential of trade zakat, the Fiqh of zakat on trade, and practical methods for calculating and paying zakat. The findings highlight that zakat administration significantly impact SMEs’ willingness to pay zakat, while attitudes toward zakat and religiosity also play crucial roles. Additionally, the results show that attitude and zakat literacy do not affect SMEs’ willingness to pay zakat. The program’s evaluation demonstrates that strengthening zakat literacy and improving zakat administration can encourage SMEs to fulfil their zakat obligations, contributing to poverty alleviation and socio-economic development. These findings offer valuable insights for optimizing zakat collection and utilization to maximize its potential in supporting community welfare.